Analisis Vegetasi Tumbuhan di Sekitar Mata Air Pada Dataran Tinggi dan Rendah Sebagai Upaya Konservasi Mata Air di Kabupaten Wonogiri, Provinsi Jawa Tengah - Yuliantoro, Dody; Frianto, Dodi (Universitas Riau, 2019)
Wonogiri Regency is one of the regencies in Central Java that suffer drought every year. This drought was triggered by the number of springs that began to